The Socioeconomic Impact of Forest Degradation on Rural Communities - Lucas Maes; Maxime Lambert; Olivier Lefevre (Journal of Selvicoltura Asean, 2024)
Forest degradation poses significant challenges to rural communities, affecting their socioeconomic conditions and overall well-being. This study investigates the multifaceted impacts of forest degradation on the livelihoods of rural populations, focusing on the loss of natural resources, economic opportunities, and social cohesion. The primary objective of this research is to analyze how declining forest health influences income sources, food security, and community dynamics in rural areas. A mixed-methods approach was employed, combining quantitative surveys with qualitative interviews in selected rural communities affected by forest degradation. Data were collected from 200 households to assess changes in income, resource availability, and social structures. The findings reveal that forest degradation has led to a decline in income-generating activities, increased vulnerability to food insecurity, and weakened community ties. Many households reported reduced access to forest products, which are crucial for their daily sustenance and economic stability. The study concludes that effective forest management and restoration strategies are essential to mitigate the negative impacts of forest degradation on rural communities. Policymakers must prioritize community engagement and sustainable practices to enhance resilience and ensure the long-term well-being of these populations.